تلبيد المساحيق السيراميكية المحضرة بطريقة التفاعل الغازي - محمود, عماد يوسف (University of Thi-Qar Journal of Science, 2014)
In this research, the ceramic powders are deposited on quartz and silicon, and we have designed and constructed furnace for sintering this powders and heated to 1100 c° , for (7) hours.